PENGUATAN BUDAYA MENELITI MELALUI PEMBELAJARAN BERBASIS RISET DI PERGURUAN TINGGI - Ardimen Ardimen; Gustina Gustina (Ta'dib, 2018)
This study focuses on the strengthening research culture through research-based learning in universities. This is a library research whose data source from reference books, scientific journals, proceedings, magazines, legislation and similar research results accessed through libraries and open journal systems. The data collection is conducted by compiling data in accordance with sub-problems which are then systematically organized. Data analysis is done by content analysis techniques to obtain theories or concepts and research results that are able to answer research problems. The results of this study indicate; 1) research is an important approach to improving the quality of learning, 2) to strengthen the culture of research at least there are four integrated focuses; (a) learning the latest research in lectures, (b) teaching research techniques or methods in each lecture taught by lecturers, (c) learning involving students to conduct research, and (d) discussion, debate or brainstorming to criticize research. 3) the benefits of PBR for students are; (a) students become usual in doing thesis because they are familiar with how to research, (b) trained to think, analyze, express and defend ideas, (c) trained to work in a planned manner, (d) trained to work hard, and (e) trained work in teams, connect with other people and collaborate.